A dinâmica e a estrutura da indústria têxtil em 2019 - Lídia Magyar (2024)
Through bibliographic research and exploratory data analysis, this dissertation aims to study the characteristics of the textile industry in 2019, taking into account neo-Schumpeterian, evolutionary, and complexity approaches. The analysis focuses on the dynamic aspect of the economy. Given the history of the First Industrial Revolution, the question arises of how different technologies overlap and shape the current configuration of the textile industry. A theoretical reinterpretation of the firm is suggested, considering evolutionary and complex elements. To build the database, a methodological proposal is presented for the analysis of data from textile firms, international trade in textile products, and patents in the sector. Finally, a description and interpretation of these data are provided within the theoretical framework developed earlier.